Abstinence-Only: Are You Not Working the Program or Is the Program Not Working for You?. Issue 3 (3rd July 2018) - LEE, HEATHER SOPHIA; O'Malley, Denalee
Abstract : Low retention rates are common in substance use treatment programs. The dominant model of service delivery in the United States is abstinence-only, a high-threshold service delivery model requiring abstinence. What "doesn't work" for the client—from the client point of view—is an overlooked source of insight about client engagement and disengagement. We report client counter-narratives about the choice to disengage from abstinence-based services, shifting from a story of "dropouts" to one of self-respect. Understanding why clients choose to disengage from treatment can help us as practitioners to "meet clients where they are" and enhance engagement in substance abuse treatment.